Peran Pola Asuh Orang Tua Terhadap Kemandirian Anak Usia Dini - Berta Yulinda Suan; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Early childhood independence is the ability of early childhood to be able to carry out daily activities in accordance with the child's developmental stages and capacities without depending on other people. Early childhood independence is influenced by parents' parenting patterns as a way of educating and guiding children to reach optimal stages of development. This research aims to determine the influence of parenting patterns on the independence of children aged 5-6 years in Kiuoni Village, Fatuleu District, Kupang Regency. This research uses quantitative methods. The data collection tool uses a parenting style scale and an early childhood independence scale. The respondents for this research were 50 children aged 5 - 6 years who were parents of early childhood children using a total sampling technique in two PAUDs in Kiuoni Village, Fatuleu District. The data analysis technique uses simple linear regression analysis. The results of this study prove that parental parenting has a positive and significant effect on the social development of children aged 5 - 6 years by 27.5%. It is hoped that children's parents can create positive parenting patterns to increase children's independence at an early age.